2016
DOI: 10.1515/aoa-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Measurement of Temperature Rise in Breast Cyst and in Neighbouring Tissues as a Method of Tissue Differentiation

Abstract: Texture of ultrasound images contain information about the properties of examined tissues. The analysis of statistical properties of backscattered ultrasonic echoes has been recently successfully applied to differentiate healthy breast tissue from the benign and malignant lesions. We propose a novel procedure of tissue characterization based on acquiring backscattered echoes from the heated breast. We have proved that the temperature increase inside the breast modifies the intensity, spectrum of the backscatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The parameters of the : Specific heat of blood Although the Pennes equation is not perfect (Weinbaum et al, 1984), due to its compatibility with analytical implementation, it is widely preferred and used for thermal model of living tissue. Due to the imperfect Pennes equation, new methods of tissue characterization have been investigated (Gambin et al, 2016), one of which is based on backscattered echoes of heated breast and integrated with statistical analysis techniques. It has been demonstrated that an increase in breast temperature modifies three parameters of the samples: "the intensity, the spectrum of echo signals and the probability density functions" (Gambin et al, 2016).…”
Section: Bioheat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of the : Specific heat of blood Although the Pennes equation is not perfect (Weinbaum et al, 1984), due to its compatibility with analytical implementation, it is widely preferred and used for thermal model of living tissue. Due to the imperfect Pennes equation, new methods of tissue characterization have been investigated (Gambin et al, 2016), one of which is based on backscattered echoes of heated breast and integrated with statistical analysis techniques. It has been demonstrated that an increase in breast temperature modifies three parameters of the samples: "the intensity, the spectrum of echo signals and the probability density functions" (Gambin et al, 2016).…”
Section: Bioheat Transfermentioning
confidence: 99%
“…Due to the imperfect Pennes equation, new methods of tissue characterization have been investigated (Gambin et al, 2016), one of which is based on backscattered echoes of heated breast and integrated with statistical analysis techniques. It has been demonstrated that an increase in breast temperature modifies three parameters of the samples: "the intensity, the spectrum of echo signals and the probability density functions" (Gambin et al, 2016).…”
Section: Bioheat Transfermentioning
confidence: 99%
“…Existing models of ultrasound scattering allow obtaining numerical parameters describing the number of scatterers and their spatial distribution from the information contained in the characteristics of the enveloping echo signal. The work [17] describes the characteristics of the most commonly used mod els of ultrasound scattering. The simplest scattering model is a discrete model, in which a wave propagates in a homogeneous medium with inclusions whose properties depend on the properties of this medium.…”
Section: Introductionmentioning
confidence: 99%
“…The Kdistribution models the case when the number of scatterers is itself a random variable, which is modeled as a Poisson distribution, the local mean of which is a gamma dis tribution [20]. The Kdistribution is formed by joining two separate probability distributions [17]. The model used to rep resent the observed intensity X involves the union of two gam ma distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation